The Trigger of SMEs Performance: Considering Islamic Financial Literacy, Financial Access, and Technical Support - Abdillah, Aldi Reza; Febriyanto, Ahmad (Universitas Siliwangi, 2024)
Introduction to The Problem: MSMEs are crucial for economic growth and job creation, but they face challenges like limited financial literacy, access to capital, and inadequate management systems. Despite resilience during crises, many struggle with financial management and growth. A multifaceted approach involving financial education, access to finance, and infrastructure is essential to fully harness their potential.Purpose/Objective Study: This research aims to analyze the influence of Islamic financial literacy, access to Islamic financial institutions, management control systems, and technical support on the performance of MSMEs Design/Methodology/Approach: The sample selection for this research uses purposive sampling which resulted in a sample of 115 respondents domiciled in the Pangkah District, Tegal Regency. This research is a quantitative study. Primary data were obtained through questionnaires, and the analysis method used was multiple linear regression. Panel data tested using SPSS.Findings: The results show that Islamic financial literacy, management control systems, and technical support have a positive and significant effect on MSMEs' performance, while access to Islamic financial institutions does not affect MSMEs' performance.